MODEL REGRESI LINIER PENGARUH STANDAR TEKNIS JALAN TERHADAP KECELAKAAN LALU LINTAS PADA JALAN PROVINSI (STUDI KASUS : RUAS JALAN PEMALANG – PURBALINGGA) - Iqbal Maulana; Rachmat Mudiyono; Abdul Rochim (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2024)
In the 2016-2021, there were 12 accidents with 22 deaths and 107 injuries on the Pemalang – Purbalingga road section. One of the factors causing accidents is the lack of attention to infrastructure that meets safety aspects. Even though the number of accidents caused by infrastructure is relatively small when compared to the human error (human) and vehicle (facility) factors, serious attention must still be paid. Traffic accidents caused by a lack of road infrastructure are generally caused by an inaccurate road geometric design, poor road surface conditions, lack of visibility and so on. Therefore the research aims to find accident-prone locations, the causes of accidents from the standard values of road technical requirements and accident regression models. The results of this study. Segments that are categorized as accident-prone locations are STA 32+000, 34+000, 36+000, 47+000 and 48+000. Substandard grades will be the cause of traffic accidents based on road technical requirements. The regression model that can be used to predict the number of accidents on provincial roads according to the variables examined in this study is: Y = -2.618 + 0.049 Grade – 0.019 X Slope – 0.008 H Curv – 0.417 V Curv + 0.264 road width + 0.081 condition IRI roads + 0.014 PCI Road Conditions